Sodium polyacrylate-derived porous carbon nanosheets for high-performance lithium–sulfur batteries. Issue 4 (27th February 2019) - Meng, Fancheng; Fan, Xiaojing; Xing, Aiming; Liu, Han; Lin, Changhao; Wang, Zhuangzhuang; Xu, Lingsong; Zheng, Lianxi; Liu, Jiehua
Abstract : A lithium–sulfur battery with a cathode material recycled from the superabsorbent polymer PAAS embedded in baby diapers. Abstract : Here we report a green and sustainable approach to transform sodium polyacrylate into hierarchically porous carbon nanosheet (HPCNS) structured lithium–sulfur battery cathodes. With an appropriate sulfur (S) loading and reduced graphene oxide (RGO) modification, the HPCNS/S@RGO hybrid yields a reversible capacity of 1262 mA h g −1 at 0.5C for the first cycle and retains 690 mA h g −1 over 200 cycles.